2007
DOI: 10.1002/chem.200700665
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Fluorescence Contrast Relationship in Cyanine DNA Intercalators: Toward Rational Dye Design

Abstract: The fluorescence enhancement mechanisms of a series of DNA stains of the oxazole yellow (YO) family have been investigated in detail using steady‐state and ultrafast time‐resolved fluorescence spectroscopy. The strong increase in the fluorescence quantum yield of these dyes upon DNA binding is shown to originate from the inhibition of two distinct processes: 1) isomerisation through large‐amplitude motion that non‐radiatively deactivates the excited state within a few picoseconds and 2) formation of weakly emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 63 publications
2
51
0
Order By: Relevance
“…This aspect is particularly important for the optimization of the fluorescence enhancement of DNA probes. 11 By contrast to all nonaggregated dyes and H-dimers, the J-aggregates formed with YOSAC3 in buffered aqueous solutions are much more fluorescent. The J-aggregate fluorescence spectrum exhibits a narrow band centered at 540 nm and a broader band at 620 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect is particularly important for the optimization of the fluorescence enhancement of DNA probes. 11 By contrast to all nonaggregated dyes and H-dimers, the J-aggregates formed with YOSAC3 in buffered aqueous solutions are much more fluorescent. The J-aggregate fluorescence spectrum exhibits a narrow band centered at 540 nm and a broader band at 620 nm.…”
Section: Resultsmentioning
confidence: 99%
“…These differences can be ascribed to the propensity of singly charged dyes to aggregate. 11 These fluorescence spectra can be considered as being due to two emitting species: nonaggregated dyes with a very short fluorescence lifetime and a spectrum that should be essentially mirror image of the absorption spectrum and H-dimers with a longer lifetime but with a small radiative rate constant due to the excitonic coupling and a broad, red-shifted fluorescence spectrum as observed with YOYO dyes in water. 9 The fluorescence spectra of YO-PRO-1 and YOSAC2 are dominated by the emission from the nonaggregated dyes.…”
Section: Resultsmentioning
confidence: 99%
“…[17] We have shown that two different mechanisms are responsible for this fluorescence enhancement upon DNA binding. [13,18,19] In water, these dyes tend to form dimeric H-type aggregates, which are non-fluorescent because of excitonic interaction between the chromophoric units. [13] On the other hand, the non-aggregated dyes undergo ultrafast non-radiative deactivation via an isomerization process involving a large-amplitude torsional motion, which takes place with a time constant of 3 − 6 ps depending on the dye structure (Fig.…”
Section: Inter-and Intramolecular Quenchingmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30] Twisting of the methine bonds in the excited state is predicted to lower the potential energy of the excited state, and to lead to charge-localized (for neutral dyes, charge-separated) states from which internal conversion is possible due to a reduced adiabatic energy gap. 31,32 In a) seth.olsen@uq.edu.au.…”
Section: Introductionmentioning
confidence: 99%